《西游记》的叙事技巧 ：以唐僧的三个徒儿形象塑造为例 = Exploring the narrative techniques of the novel “Journey to the West” : using the portrayal of the Tang monk’s disciples as example - 戴欣怡 Tee, Xinyi (2013)
此论文研究以文本细读的方法，从作者吴承恩如何塑造唐僧三个徒儿的形象，来看作者的叙事技巧。本文将通过两种不同的角度来看作者对三个小说人物的形象塑 造。首先,从三个徒弟最突出的性格特征切入，孙悟空的勇敢、猪八戒的贪心和沙僧的和谐性情。再来观察三人在特定情况下的表现，如三人之间的日常互动和面对困境时 的反应。在观察与分析后，笔者认为作者的叙事带有“奇幻性”、“奇趣性”和“诙谐性”的描写技巧，而这也是《西游记》这部小说之所以会成为脍炙人口的一部古典小说。Through text reading, this thesis paper explores the author Wu Cheng-en’s narrative skills through analyzing the way he sculpted the images of Tang monk’s three disciples. The writer looks at the way the author sculpted the images of the three disciples from two perspectives. Firstly, it is through observing how the author wrote the most prominent character traits of the three disciples, such as Sun Wukong’s braveness, Zhu Bajie’s greediness and Friar Sand’s harmony temperament. Secondly, it is through observing how the author wrote the disciples’ reactions in different scenarios such as during their interactions and when they faced adversities. After much observations and analysis, the writer finds that the author had used narrative skills which are fancying, enthralling and amusing, which is the reason why the novel “Journey to the West” is a popular classic novel.